Small-conductance calcium-activated potassium (SK) channels in the amygdala mediate pain-inhibiting effects of clinically available riluzole in a rat model of arthritis pain - Thompson, Jeremy M. (Mol Pain, 2015)
BACKGROUND: Arthritis pain is an important healthcare issue with significant emotional and affective consequences. Here we focus on potentially beneficial effects of activating small-conductance calcium-activated potassium (SK) channels in the amygdala, a brain center of emotions that plays an important role in central pain modulation and processing. SK channels have been reported to regulate neuronal activity in the central amygdala (CeA, output nucleus). We tested the effects of riluzole, a clinically available drug for the treatment of amyotrophic lateral sclerosis, for the following reasons. Actions of riluzole include activation of SK channels. Evidence in the literature suggests that riluzole may have antinociceptive effects through an action in the brain but not the spinal cord. Mechanism and site of action of riluzole remain to be determined. Here we tested the hypothesis that riluzole inhibits pain behaviors by acting on SK channels in the CeA in an arthritis pain model. RESULTS: Systemic (intraperitoneal) application of riluzole (8 mg/kg) inhibited audible (nocifensive response) and ultrasonic (averse affective response) vocalizations of adult rats with arthritis (5 h postinduction of a kaolin-carrageenan monoarthritis in the knee) but did not affect spinal withdrawal thresholds, which is consistent with a supraspinal action. Stereotaxic administration of riluzole into the CeA by microdialysis (1 mM, concentration in the microdialysis fiber, 15 min) also inhibited vocalizations, confirming the CeA as a site of action of riluzole. Stereotaxic administration of a selective SK channel blocker (apamin, 1 µM, concentration in the microdialysis fiber, 15 min) into the CeA had no effect by itself but inhibited the effect of systemic riluzole on vocalizations. Off-site administration of apamin into the basolateral amygdala (BLA) as a placement control or stereotaxic application of a selective blocker of large-conductance calcium-activated potassium (BK) channels (charybdotoxin, 1 µM, concentration in the microdialysis fiber, 15 min) into the CeA did not affect the inhibitory effects of systemically applied riluzole. CONCLUSIONS: The results suggest that riluzole can inhibit supraspinally organized pain behaviors in an arthritis model by activating SK, but not BK, channels in the amygdala (CeA but not BLA).